KAJIAN PEMANFAATAN TANAMAN BERKHASIAT OBAT PADA SISTEM PENGOBATAN TRADISIONAL MASYARAKAT DI PROVINSI MALUKU UTARA - Muhammad Haji Noh; Monissa A. Hi. Djafar; Hamidah Rahman; Badryah Abbas; Musiana . (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2020)
Traditional medicine is a part of culture and it is valued as a local wisdom of the community. Knowledge about medicinal uses of plants is generally passed down from generation to generation both verbally and from ancient manuscripts found from various regions in Indonesia. In North Maluku, there are several traditional medical practices using medicinal plants that are still ongoing.This study aims to obtain a descriptive data of traditional medical practices using medicinal plants in North Maluku using a systematic review method. Scientific data was obtained from online search on Google Scholar. The keywords used are